DETERMINING THE PHYSIOCHEMICAL AND PHYTOCHEMICAL PROPERTIES OF LOCAL NIGERIAN WHITE MELON SEED FLOUR - Okorie, Peter Anyigor (International Journal of Research -GRANTHAALAYAH, 2018)
The functional properties, proximate composition and phytochemical characteristics of a local Nigerian white melon seed flour was determine in this study. Foaming capacity, emulsion capacity, oil absorption, water absorption, and bulk density tests were conducted. The moisture, protein, fat, fibre, ash, carbohydrate, flavonoid, saponin, carotenoid and alkaloid contents of the flour were determined. The results show that the functional properties of the flour are: foaming capacity 0.03 %, emulsion capacity 60.50 %, oil absorption capacity 34.10 %, water absorption capacity 18.60 % and bulk density 1.62 g/ml. The proximate composition of the flour are: carbohydrate 58.43 %, protein 32.55 %, moisture 1.70 %, fat 29.00 %, crude fibre 6.15 % and ash 0.85 %. The flour has the following phytochemical composition: flavonoid 3.13 %, saponin 4.88 %, carotenoid 1.80 % and alkaloid 5.90 %. The analysis revealed that the flour could be used in soup making and infant food formulation. It could also be useful for prevention and cure of heart related diseases.